The Columbia guide to contemporary African American fiction - Dickson-Carr, Darryl, 1968- (Columbia guides to literature since 1945., 2005)
From Ishmael Reed and Toni Morrison to Colson Whitehead and Terry McMillan, Darryl Dickson-Carr offers a definitive guide to contemporary African American literature. This volume-the only reference work devoted exclusively to African American fiction of the last thirty-five years-presents a wealth of factual and interpretive information about the major authors, texts, movements, and ideas that have shaped contemporary African American fiction. In more than 160 concise entries, arranged alphabetically, Dickson-Carr discusses the careers, works, and critical receptions of Alice Walker, Glor.